The tennis common content knowledge measure validation. (August 2021) - Tsuda, Emi; Ward, Phillip; Kim, Junyoung; He, Yaohui; Sazama, Debra; Brian, Ali
The purpose of this study was to develop a valid and reliable common content knowledge (CCK) instrument for pre-service teachers who teach fundamental tennis in secondary schools. The instrument, called the tennis CCK test for pre-service teachers (CCK-Tennis), was administered to 117 undergraduate students who were enrolled in physical education (PE) teacher education programmes at three universities in the United States. Two tennis content experts developed the CCK-Tennis and five in-service teachers reviewed the test to establish content validity. A total of 10 pre-service teachers took the test for pilot testing. The data were analysed using Rasch statistics (Linacre, 2011; Rasch, 1980). The authors judged the unidimensionality of the CCK-Tennis using the unexplained variance in the first contrast (2.59) and the standardized residual contrast one plot (-0.4 to 0.4). These data provided evidence that the test is unidimensional and measures tennis CCK. The results of infit (0.8 to 1.2) and outfit (0.5 to 1.5) mean square residuals showed that the difficulty of the questions matches respondents' knowledge levels. The item (5.32, Cronbach's α = 0.97) and person (1.71, Cronbach's α = 0.72) separation index and the Wright map showed that there are low to high knowledge levels of the respondents who took the test. The results illustrate that the CCK-Tennis is a robust, valid, and reliable tool that people can use in teacher education. Having valid and reliable measures for CCK is an essential step to improve teachers' instructional effectiveness from the area of content knowledge.